2020
DOI: 10.1016/j.carbpol.2020.116363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial properties of new chitosan derivatives containing guanidinium groups

Abstract: Highlights New chitosan derivatives bearing guanidinium functions were prepared and characterized.  The four derivatives displayed improved antimicrobial activity in comparison with neat chitosan.  Biosourced and renewable chitosan derivatives could be applied as antimicrobial surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 36 publications
0
44
0
1
Order By: Relevance
“…For example, one study showed that the performance and health of Nile tilapia ( Oreochromis niloticus ) were significantly improved when chitosan nanoparticles were loaded in basic diets (one gram per kilogram) [ 20 ]. Similarly, Khani Oushani et al found that diets supplemented with 0.05 g kg −1 of nano-chitosan and clinoptilolite could improve the growth performance and immune parameters of rainbow trout ( Oncorhynchus mykiss ) [ 21 , 22 , 23 , 24 ]. However, these studies mentioned above principally aimed to improve the immunity of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study showed that the performance and health of Nile tilapia ( Oreochromis niloticus ) were significantly improved when chitosan nanoparticles were loaded in basic diets (one gram per kilogram) [ 20 ]. Similarly, Khani Oushani et al found that diets supplemented with 0.05 g kg −1 of nano-chitosan and clinoptilolite could improve the growth performance and immune parameters of rainbow trout ( Oncorhynchus mykiss ) [ 21 , 22 , 23 , 24 ]. However, these studies mentioned above principally aimed to improve the immunity of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…In the spectrum of CA‐FeNPs, the absorption peak at around 2875 cm −1 can be attributed to the C–H symmetrical stretch 49 . The peaks at 1637 and 1559 cm −1 are ascribed to the C=O stretching (amide I) and –NH stretching (amide II), respectively 50 . The peak at 577 cm −1 is from Fe–O bonding, 28 demonstrating the successful incorporation of FeNPs.…”
Section: Resultsmentioning
confidence: 96%
“…Different chitosan sources have different molecular weight, deacetylation grade, and emulsion abilities from the chitosan of a crab shell. The chitosan's molecular weight, length, deacetylation levels, and the replacement position of glucosamine chitosan units, pH chitosan solution, and target organisms can affect its inhibitory efficacy (Salama et al, 2020).…”
Section: Chitosanmentioning
confidence: 99%